Zero to infinity [videorecording (DVD)] - McCabe, Daniel (PBS, 2023)
Tells the story of a mathematician's quest to understand numbers. In her day job, professor of statistics Talithia Williams ponders the power of data looking for answers and spotting patterns in huge collections of numbers. But as the anticipated host, she takes a step back and turns her attention to the digits themselves exploring their origins and discovering the wonder that arises from simple, yet profound concepts like nothingness, infinity, and the mysteries embedded in special numbers like primes.